Ellipticity dependence of 400 nm-driven high harmonic generation - Khan, Sabih D.; Cheng, Yan; Möller, Max; Zhao, Kun; Zhao, Baozhen; Chini, Michael; Paulus, Gerhard. G.; Chang, Zenghu (My University, 2011)
We studied the dependence of high harmonic generation efficiency on the ellipticity of 400 nm driving laser pulses at 7.7 × 1014 W/cm2 and compared it with the 800 nm driving laser under the same conditions. The measured decrease of high harmonic yield with the ellipticity of the 400 nm laser is ∼1.5 times slower that of the 800 nm, which agrees well with theoretical predictions based on a semi-classical model. The results indicate that it is feasible to use the generalized double optical gating with 400 nm lasers for extracting single attosecond pulses with high efficiency.